Fonction sexuelle masculine et sexualité féminine - Giami, Alain (Communications, 2007)
Major changes have occurred in male and female sexual function/dysfunction research and treatments. Male erectile dysfunction has been re-conceptualized as an organic dysfunction, which marks a dramatic shift from previous conceptions of psychogenic impotence developed during the 60' and the 70's. This shift is based on major scientific discoveries, and pharmacological advances that took place since the early 80's under the influence of North American urologists. The release of sildenafil in 1998 was thecorner stone of a new paradigm of treatments focusing on male penile activity, far remote from any psychological approaches. More recently, the same group of urologists started to reconsider Female Sexual Dysfunction using the same organic/biological model of sexual function. New pharmaceutical products are currently under trial for the treatment of this new category of female sexual disorder. But as opposed to the absence of public adverse reaction to the development of this approach of male function, many voices raised to oppose this new conception of female function. A major discussion took place in the British Medical Journal (2003) stating that female sexual function was not organically driven, but rather determined by the social, psychological and interpersonal context of female sexual activity and relations. One of the major dimension of this discussion opposed the so-called "simplicity" of male sexual function to the "complexity" of female sexual function.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; essentialisme; europe; féminisme radical; patriarcat; premier cycle; pédagogie; périodes historiques; recherche; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

L’effet Matthieu Mathilda en sciences - Rossiter, Margaret W. (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2003)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; approches et analyses; cours; discipline; discours dominant; europe; patriarcat; premier cycle; pédagogie; périodes historiques; régions géographiques; science; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

Scientificité et politique aujourd’hui : un regard féministe - Puig de la Bellacasa, María (Nouvelles Questions Féministes, 2003)
La richesse de la recherche féministe est en grande partie tributaire de la tension entre scientificité et engagement politique. Elle défie ainsi les définitions modernes de la scientificité et notamment la séparation entre science et politique. Cependant les enjeux liés à cette tension sont historiquement situés. Cet article propose une réflexion sur deux processus actuels qui peuvent affecter négativement cette singularité de la pensée féministe. D’une part, la précarisation du travail et la dégradation des rapports dans le monde académique. D’autre part, l’exigence actuelle d’une « pertinence sociale » des « produits » académiques.
Keywords: 1900-1999; 1970-1979; 1990-1999; angleterre; approches et analyses; cours; discipline; discours dominant; europe; france; histoire et politique; inégalités; patriarcat; premier cycle; pédagogie; périodes historiques; régions géographiques; science; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

Nos amis et nous. Les fondements cachés de quelques discours pseudo-féministes - Delphy, Christine (Questions Féministes, 1977)
Keywords: 1900-1999; 1970-1979; approches et analyses; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; inégalités; militance; patriarcat; premier cycle; pédagogie; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques